Immunomodulatory Activity of Eurycoma longifolia (Simaroubaceae) Roots and Acalypha indica (Euphorbiaceae) Leaves Methanol Extracts on BALB/c Mice - Yee Lee, Siew
Immunomodulation referred to the change, either stimulate or suppress the immune system. Based on the mechanism of action, immunomodulators can be divided into immunostimulators and immunosuppressants. Traditionally, there were a lot of medicinal plants used to modulate immune system in order to fight against many disease including infectious disease and cancer such as Eurycoma longifolia and Acalypha indica. Therefore, this research was done to investigate the immunomodulatory activity of E. longifolia root and A. indica leave methanol extract on BALB/c mice to provide a rationale used of E. longifolia and A. indica as traditional medicine. This research was started with identity determination of plants and extracts preparation using Reflux apparatus with methanol as solvent. Extracts were then concentrated using rotary evaporator. Dried extracts were prepared by adding lactose. Research was then followed by oral administration of the dried extracts that had been suspended in Na CMC to the mice. Two doses of extract were tested for each plant i.e. E. longifolia at dose 0.65 and 1.30 mg/kg bw and A. indica at dose 32.50 and 65.00 mg/kg bw. The parameters used to evaluate the immunomodulatory activity including ratio of phagocytic index through carbon clearance assay, organ index of liver, spleen and thymus and the antibody production through HA titre using SRBC as immunogen. Results from each parameters were compared to control group. Based on the results, both E. longifolia and A. indica showed high immunostimulatory effect indicated through higher ratio of phagocytic index (ratio>1.5) compared to control. In organ index, there was significant increased (p<0.05) and increased but not significantly (p<0.1) in spleen index in E. longifolia extract treated group at dose of 0.65 and 1.30 mg/kg bw respectively. The spleen and thymus index were significant increased (p<0.05) in A. indica extract treated group at dose of 65.00 mg/kg bw. While in HA titre, all extract treated groups showed higher antibody titre compared to control group. Based on correction to water content in extracts, it can be concluded that both doses of E. longifolia extract which were equivalent with extract dose for human at 0.06 and 0.12 mg/kg bw and A. indica extract equivalent with extract dose for human at 3.09 and 6.18 mg/kg bw, had potential to be further developed as immunostimulating agent. Since extracts were aimed in daily uses for functioning as immunostimulating agent, hence the toxicity of the methanol extracts of E. longifolia roots and A. indica leaves should be evaluated.